Involvement of Mobile phones as a source for Nosocomial infections - Shukla, Priyanka; Khalid, Bushra; Yaqoob, Shadma; Ahmad, Sharique (Asian Journal of Medical Sciences, 2021)
Background: Mobile phones are communication devices for communication nowadays and have emerged as a need of our life. Mobile phones also act as a reservoir for microorganisms. Human skin, wallets, bags, environment and food items are major sources of contamination for mobile phones. Medical students, healthcare workers and other non-teaching staff nowadays use mobile phones for communication in the workplace. Mobile phone contamination spreads from surfaces to hands. Aims and Objective: Our study was aimed to investigate the contamination of mobile phones by pathogens among health care workers. The objective of this study was to document for the role of mobile phones as sources in nosocomial infections. Materials and Methods: The study was done in Department of Microbiology and Pathology, Era’s Lucknow Medical College and Hospital, including teaching staffs from hospital and college, health care workers in all laboratories and wards. A total of 200 swab samples from various mobile phones of medical and technical staff of various wards, Outpatient Department Treatment, laboratories was collected after taking informed written consent from them. Culture was done on Blood Agar, MacConkey Agar, and Sabouraud’s dextrose agar. After overnight incubation, colonies were identified by Gram’s stain and Biochemical tests. Results: Highest mobile phone users are medical students, residents followed by teaching faculty. Smart phones or touch screen mobiles were used by maximum ie.90.5%. Among the isolated bacteria, Bacillus (39.5%), CONS (19%), E.coli (15.5%), Klebsiella (10.5%), Pseudomonas (5.5%), Staphylococcus aureus (4%), Enterococcus (2.5%). No growth was seen in 3.5%mobile phone sample cultures. Not a single fungal pathogen was isolated. Conclusion: The findings is the present study suggests that the mobile phones used by medical staff and health care workers act as source of transmission vehicles for pathogenic microorganisms.